Oyster shell, zeolite, and red mud binding mechanisms and their applicability for immobilizing toxic metals in diverse contaminated scenarios - Torres Quiroz, Cecilia (2021)
Descargue el texto completo en el repositorio institucional de la Seoul National University: https://hdl.handle.net/10371/178197